Faktor-Faktor yang Mempengaruhi Repeat Breeding pada Sapi Potong - Devi Tamara (Habitat: Jurnal ilmiah ilmu Hewani dan Peternakan, 2026)
Repeat breeding is a reproductive disorder in beef cattle characterized by the failure to conceive after three or more matings or artificial inseminations (AI), despite normal estrus cycles and no obvious reproductive abnormalities. This condition is one of the causes of low reproductive efficiency and economic losses in beef cattle farms due to prolonged calving intervals, increased insemination costs, and reduced livestock productivity. This article aims to examine various factors influencing the occurrence of repeat breeding in beef cattle through a literature review of various recent studies. The results indicate that repeat breeding is influenced by reproductive management, nutrition, reproductive health, environmental conditions, and farmer factors. Accurate estrus detection and insemination timing are important factors determining successful conception. In addition, low feed quality, nutritional imbalances, reproductive tract infections, and poor barn sanitation also increase the risk of repeat breeding. The knowledge and experience of farmers also play a role in managing livestock reproduction. Therefore, efforts to prevent repeat breeding require an integrated approach through improved management of husbandry, reproduction, livestock health, and increased farmer capacity.